2016
DOI: 10.4102/koedoe.v58i1.1348
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of traditional ecological knowledge and beliefs in the utilisation of important plant species: The case of Buhanga sacred forest, Rwanda

Abstract: Traditional ecological knowledge is an integrated part of the African people and indeed the Rwandese for cultural purpose. Buhanga sacred forest is a relict forest of tremendous ecological importance to Rwandan society located in Musanze District. The aim of this study was to assess the traditional ecological knowledge and belief in the utilisation of some important plant species for the conservation of Buhanga sacred forest. Ecological information about ethnomedicinal and traditional practices were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Thus, it appears that the local community members either lacked IEK or simply lost the knowledge that they acquired from the parents and grandparents. The use of IEK has been used to assess the knowledge and beliefs in the utilization of important plant species (Irakiza et al, 2016). The loss of IEK among local community members is now regarded as one of the threats in conservation of indigenous plant species (Gómez-Baggethun et al, 2013;Gómez-Baggethun et al, 2012;Reyes-García et al, 2014;Tang and Gavin, 2016;Aswani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it appears that the local community members either lacked IEK or simply lost the knowledge that they acquired from the parents and grandparents. The use of IEK has been used to assess the knowledge and beliefs in the utilization of important plant species (Irakiza et al, 2016). The loss of IEK among local community members is now regarded as one of the threats in conservation of indigenous plant species (Gómez-Baggethun et al, 2013;Gómez-Baggethun et al, 2012;Reyes-García et al, 2014;Tang and Gavin, 2016;Aswani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The IEK has been used to assess knowledge and beliefs in the utilization of important plant species (Irakiza et al, 2016). Among the 48 species identified, the elders were able to identify 30 use groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 600 Rwandan Indigenous plant species are used as herbs in cosmetics, agriculture, food and beverage production, traditional medicine, and construction (Rwanda Environment Management Authority, 2019). In the areas surrounding Buhanga Forest in the Northern Province-specifically in Bikara Cell, Nkotsi Sector, Musanze District-around 45 herbs belonging to 28 families have been identified as useful in Indigenous medicine (Runyambo et al, 2016). In Buhanga Forest, six plant species have been identified that are traditionally used in treating cattle diseases, while another three species have been identified as being used for the traditional treatment of both cattle and human diseases (Runyambo et al, 2016).…”
Section: Rwandan Livestock Farming and Indigenous Treatmentsmentioning
confidence: 99%
“…These practices includes among others, removal of few roots from plants, harvesting of a bark that is the size of the palm of one's hand, taboos and social controls promoting sustainable harvesting of plants [18]. Studies conducted in countries such as Kenya [19], Ghana [20], Lesotho [21], Zimbabwe [22], Nigeria [3], Tanzania [23], Uganda [24], Benin and Gabon [25], Rwanda [26], and Ethiopia [27] indicated that these practices are very common among the indigenous communities and have evolved through the historical interaction of people and their environment.…”
Section: Introductionmentioning
confidence: 99%